Danger in Ancient Rome - Messner, Kate.; McMorris, Kelley (New York : Scholastic Inc., 2015)
The mysterious box that Ranger the golden retriever found in the garden transports him back to first century Rome, where he must rescue Marcus, a young servant boy, and Quintus, a volunteer gladiator, from the brutal world of the Colosseum.
Includes bibliographical references.
Kirkus Review, March 2015.
4.3
3-6
610L
Keywords: Colosseum (Rome, Italy) -- Juvenile fiction; Colosseum (Rome, Italy) -- Fiction; Colosseum (Rome, Italy) -- Fiction; Golden retriever -- Juvenile fiction; Time travel -- Juvenile fiction; Gladiators -- Rome -- Juvenile fiction; Golden retriever -- Fiction; Dogs -- Fiction; Time travel -- Fiction; Gladiators -- Fiction; Golden retrievers -- Fiction; Dogs -- Fiction; Time travel -- Fiction; Gladiators -- Fiction; Time travel -- Fiction; Adventure and adventurers -- Fiction; Rome -- History -- Fiction; Action and adventure fiction